La Crouzade V-VI (Aude, France) : un des plus anciens fossiles d'anatomie moderne en Europe occidentale - Dominique Henry-Gambier; Dominique Sacchi (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
The frontal bone (La Crouzade V) and the maxilla (La Crouzade VI) of an adult were discovered by T. and P. Héléna at the beginning of the 20th century in the cave of La Crouzade (Aude). The anthropological analysis of these remains shows that they belong to Homo sapiens sapiens. The revision of the stratigraphy and the associated industry had led to attribute this fossil to an early phase of the Aurignacian. An AMS date (ERL 9415—30640 ± 640 BP) from the maxilla places this fossil within the time span of 31 920-29 360 BP at two standard deviations, and hence among the oldest specimens of modern man in Europe, but it also distances it considerably from the earliest phases of the Aurignacian.